2007
DOI: 10.1016/j.jmaa.2006.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Necessary optimality conditions for differential–difference inclusions with state constraints

Abstract: We consider the Mayer optimal control problem with dynamics given by a nonconvex differentialdifference inclusion, whose trajectories are constrained to a closed set. Necessary optimality conditions in the form of the maximum principle are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Furthermore, the methods of [6] and [7] cannot be adapted to cover problems with time delays in the control, because it is not possible to express a controlled delay differential equation (with delays in the control) as a delay differential inclusion (which can take account only of delays in the state).[7] allows both distributed and discrete delays (in the state variable), whereas we allow only discrete delays (in both state and control variables). Necessary conditions for optimal control problems involving differential inclusions are also provided in [3] and [15] for fixed time optimal control problems involving a single time delay in the state. We mention that Warga [19] showed that a broad class of optimal control problems involving delays and/or functional differential equations, distinct from the problems considered in this paper, can be fitted to an abstract framework within which nonsmooth necessary conditions can be derived; [19] requires a special 'additively-coupled' structure for the control delay dependence.…”
mentioning
confidence: 99%
“…Furthermore, the methods of [6] and [7] cannot be adapted to cover problems with time delays in the control, because it is not possible to express a controlled delay differential equation (with delays in the control) as a delay differential inclusion (which can take account only of delays in the state).[7] allows both distributed and discrete delays (in the state variable), whereas we allow only discrete delays (in both state and control variables). Necessary conditions for optimal control problems involving differential inclusions are also provided in [3] and [15] for fixed time optimal control problems involving a single time delay in the state. We mention that Warga [19] showed that a broad class of optimal control problems involving delays and/or functional differential equations, distinct from the problems considered in this paper, can be fitted to an abstract framework within which nonsmooth necessary conditions can be derived; [19] requires a special 'additively-coupled' structure for the control delay dependence.…”
mentioning
confidence: 99%
“…Note one paper [7] where an algorithm to solve boundary value problems for differential inclusions was constructed. Let us also give some references [8], [9], [10], [11] with optimality conditions in problems with differential inclusion. In these papers differential inclusions of a rather general form are considered.…”
Section: Introductionmentioning
confidence: 99%
“…where z * is the global minimizer of functional (8). So, the problem of finding an approximate solution of the original problem is reduced to the minimization of functional (8) in the space P n [0, T ].…”
Section: Reduction To An Unconstrained Minimization Problemmentioning
confidence: 99%
“…The necessary minimum conditions for differential inclusions with both convex and nonconvex multivalued mappings were explored in such papers as [18], [14], [8], [23]. More constructive necessary minimum conditions were obtained in [2], [1], [11].…”
Section: Introductionmentioning
confidence: 99%